Dissipation of Hydraulic Energy by Curved Baffle Blocks - Eloubaidy, Aziz F.; Al-Baidhani, J. H.; Ghazali, Abdul Halim (Universiti Putra Malaysia Press, 1999)
Experimental evaluation of the effects of relative size, curvature and location of curved floor baffle blocks in the dissipation of energy and control of hydraulic jump is presented. The flow over floor blocks with curved upstream edges (in plan) was described by a set of dimensionless ratios using dimensional analysis techniques. The solution was evaluated in the laboratory with respect to measurable elements of the flow. The results have indicated that, for all flow conditions, the curved blocks are generally more effective in lowering the downstream kinetic energy than regular straight edges blocks; thereby, creating optimum flow conditions having lower capacity for erosion of the downstream channel bed together with economy in structural requirements.